Teachers' Attitude Towards the Use of ChatGPT for Educational Assessment - Oluwaseyi Aina Gbolade Opesemowo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The rapid integration of AI tools like ChatGPT in education raises questions about their potential to enhance assessment methods. However, researchers have not fully explored teachers' attitudes toward adopting ChatGPT for educational assessment, especially regarding how gender, academic discipline, and years of experience influence their attitudes toward using these technologies. The study examined the effect of gender, academic discipline, and years of experience on teachers' attitudes toward using ChatGPT for educational assessment. The study employed a descriptive survey research design in administering an online survey to teachers (n = 102). Data collected were analyzed using linear regression. Results indicated that gender (β = -.536, p = .002) and academic discipline (β = .349, p = .014) significantly influenced attitudes, with male teachers and those in the Sciences showing more favourable attitudes toward ChatGPT. However, years of experience had no significant effect on attitude (β = .035, p = .616). Overall, the model was statistically significant (F(3, 98) = 6.450, p < 0.05), highlighting the importance of gender and discipline in shaping attitudes toward the use of ChatGPT for educational assessment. The study concluded that gender and academic discipline are key predictors. Other unexplored factors might influence teachers' attitudes toward adopting ChatGPT for educational assessment. Further research may consider exploring additional factors like institutional support, training, and perceived usefulness of AI tools to gain a comprehensive understanding.